Borderline Disorder: (De facto) Historical Ethnic Borders and Contemporary Conflict in Africa - Depetris-Chauvin, Emilio; Özak, Ömer (My University, 2020)
We explore the effect of historical ethnic borders on contemporary non-civil conflict in Africa. Exploiting variations across artificial regions (i.e., grids of 50x50km) within an ethnicity's historical homeland, we document that both the intensive and extensive margins of contemporary conflict are concentrated close to historical ethnic borders. Following a theory-based instrumental variable approach, which generates a plausibly exogenous ethno-spatial partition of Africa, we find that grid cells with historical ethnic borders have 27 percentage points higher probability of conflict and 7.9 percentage points higher probability of being the initial location of a conflict. We uncover several key underlying mechanisms: competition for agricultural land, population pressure, cultural similarity and weak property rights.
Keywords: Africa; Borders; Conflict; Development; Economic Development; Ethnic Borders; Ethnic Conflict; Historical Homelands; Landownership; Migration; Population Pressure; Property Rights; Territory; Thiessen Tesselation; Voronoi Tesselation